Wind Tunnel Tests and Modeling Analysis of Dynamic Boundary Layer Transition on a Blunt Cone with Continuously Increasing Reynolds Number - Shiyu ZHANG; Yan ZHANG; Jiajian ZHOU; Junbo ZHAO; Zengliang FU; Cheng SU (气体物理)
The region of boundary layer transition on a blunt cone alternates periodically with pitching motion, and simultaneously develops from end to forward due to increasing Reynolds number during flight. This dynamic process may induce instability of pitching motion. Based on the dynamic boundary layer transition test technology and continuous-Reynolds-number-increasing wind tunnel test technology, wind tunnel tests of dynamic boundary layer transition with continuously increasing Reynolds number were performed using blunt cone models with half-cone angle of 9°. Sustained oscillation and divergence of the angle of attack were measured during boundary layer transition developing on the surface of blunt cone. Based on the experimental results, it is preliminarily indicated that the coupling between development of asymmetric boundary layer transition and pitching motion leads to the oscillation and divergence of angle of attack. A dynamic boundary layer transition-induced pitching moment model was established, based on the pitching moment of static boundary layer transition and the time delay of boundary layer transition compared with pitching motion, which was measured from wind tunnel tests. The simulation results based on the induced pitching moment model reproduced the phenomenon of angle-of-attack oscillation and divergence. Meanwhile, the results indicated that the delay of pitching moment caused by the delay of boundary layer transition may be the key factor to induce the divergence of pitching motion.